Growth of Zamia Leaf Cuttings (Zamioculcas zamiifolia) with the Application of Auxin Hormone and Foliar Fertilizer on Water Media - Swandari, Tantri; Ibrahim, Rohmat Maulana; Suryanti, Sri (Universitas Pattimura, 2023)
Zamioculcas zamiifolia is an ornamental aroid plant that can be propagated vegetatively through leaf, stem, and petiole cuttings. Cultivation efforts are needed to increase the viability of cuttings as well as faster root and shoot induction, one of which is by using planting media and adding ZPT. This study aims to determine the effect of the application of the hormone auxin and foliar fertilizer on the growth of zamia leaf cuttings in aqueous media. The research was carried out at the Stiper Agricultural Institute, Yogyakarta, from June 1 to August 10, 2021. The method used was a factorial experiment arranged in a completely randomized design (CRD). The first factor is the concentration of the auxin hormone which consists of 3 levels, namely 0; 2.5; and 5 ppm. The second factor is the concentration of foliar fertilizer consisting of 4 levels, namely 0; 0.25; 0.5; and 0.75 g/l. The results showed that the 0.25 ppm auxin treatment was able to induce root elongation. Foliar fertilizers have an important influence on root formation, keeping the cuttings green, tuber induction, shoot growth percentage, and the addition of fresh weight. The most optimal concentration of foliar fertilizer is 0.5 g/l.